The analysis of trust as an Islamic estate planning instrument in Malaysia: challenges and effects - Awang, Abdul Bari; Abdullah, Muhamad Muizz; Nor Muhamad, Nasrul Hisyam (UUM Press, 2022)
Efficient and effective Islamic estate planning not only provides convenience to Muslims, but it is also capable of driving national economic progress and development. One of the instruments of Islamic estate planning is dependent on the trust instrument, which is based on civil law. The effect of not implementing the trust at an early stage can be seen in the status of property acquired, as it may not be managed effectively and may indirectly harm the beneficiary. Therefore, the present study was an attempt to identify the challenges and effects in the implementation of trust; when it has not been implemented efficiently and to look into the effects of late Islamic estate planning during one’s lifetime. The study has applied a qualitative study method by analysing previous articles, related statutes, and looking at the application of the trust instrument by trust institutions in Malaysia. To achieve the objectives of the present study, the researchers conducted interviews with officers from the Amanah Raya Berhad (ARB), which is the largest Public Trustee in Malaysia and it has just marked the 100th anniversary of its establishment this year. The finding of the study revealed that the trust instrument has a few challenges in its implementation, whether with respect to the trustee, society, and the inconsistencies of law. For example, the failure in planning when using the trust instrument will affect the family institution and the management of the property itself. In conclusion, the issue of Islamic estate planning during one’s lifetime should not be taken lightly by society as it can turn out to be detrimental to the family and the national economy.